Selective in vitro anti-melanoma activity of ursolic and oleanolic acids. (12th February 2018) - Oprean, Camelia; Ivan, Alexandra; Bojin, Florina; Cristea, Mirabela; Soica, Codruta; Drăghia, Lavinia; Caunii, Angela; Paunescu, Virgil; Tatu, Calin
Abstract: Products of natural origin have become important agents in the treatment of cancer, and the active principles of natural sources could be used in combination with chemotherapeutic agents to increase their effects and to minimize their toxicity. Oleanolic (OA) and ursolic (UA) acids are intensely studied for their promising anticancer potential. The aim of this study was focused on the in vitro toxicological effects induced by UA and OA human mesenchymal stem cells and on melanoma, one of the most frequent cancers whose incidence is increasing every year. The two compounds were tested for their cytotoxic, cell cycle arrest and pro-apoptotic effects on melanoma cells (A375 and B164A5) and mesenchymal stem cells. UA exerted a cytotoxic effect in a dose-dependent manner on melanoma cells, while OA's activity has been shown to be low or moderate. Both compounds produced alterations of the cell cycle, arresting cells in the G0/G1 phase. Furthermore, UA induced significant apoptosis through the bcl-2 genes family pathway, with the decrease of the bcl-2 gene expression. The two compounds exerted selective effects on melanoma cells with no effects on human mesenchymal stem cells. The presented results reveal the anticancer potential of UA on melanoma cells, with no detectable toxicity on the mesenchymal stem cells.